Investigating the relationship between parental weight stigma and feeding practices. (1st June 2020) - Gold, Joshua M.; Vander Weg, Mark W.
Abstract: Promoting a healthy diet in children remains a prominent public health priority. Parents have been shown to be a major influence on their children's eating behaviors, but limited research has been devoted to exploring the factors that lead parents to select certain feeding practices over others. Past research has demonstrated a link between weight stigma (i.e., prejudicial attitudes or discriminatory behavior targeted at individuals who carry excess weight) and an individual's own weight-related behaviors and outcomes, but no study has examined how parental levels of weight stigma maybe associated with a parent's preferred feeding practices. The primary objective of this study was to examine the cross-sectional associations between parental levels of weight-based stigmatization with parental feeding practices. Responses were collected on Amazon's Mechanical Turk website for n = 406 parents who 1) had at least one child aged 5–10 and 2) perceived themselves to be overweight or obese. After adjusting for relevant covariates, parental weight stigma was shown to be significantly associated with restrictive feeding practices, and verbal modeling of eating behaviors (all p s < .05). A priori exploratory mediation analysis identified concern about child weight as a significant mediator between weight stigma and parental feeding practices. A discussion of the potential limitations of this study, future directions of research, and implications of these findings are included.